Factors Associated With Nurse Preparedness in Handling Covid-19 Patients in The Installation Room Hospital Emergency Department - Putri Puspitasari; Alfian Novan Pahlevi; Suparni Suparni (JURNAL KESEHATAN : JURNAL ILMU- ILMU KEPERAWATAN, KEBIDANAN, FARMASI DAN ANALIS KESEHATAN, SEKOLAH TINGGI KESEHATAN MUHAMMADIYAH CIAMIS, 2023)
Corona virus or known as COVID-19 is a disease outbreak that can be transmitted through the respiratory tract. Based on data in Indonesia until March 25, 2022 positive 5,986,830, recovered 5,676,510, died 154,343 cases. Emergency room nurses are health workers who are at the forefront in handling infectious diseases, nurses have a higher risk of contracting COVID-19, therefore the importance of preparedness for nurses. The purpose of the study was to identify factors related to the preparedness of nurses in handling COVID-19 patients in the emergency room of one of the hospitals in the city of Bandung. This type of research is quantitative with a descriptive correlation design with a cross sectional approach.  The population in this study were nurses in the emergency room. Sample selection using total sampling technique, as many as 30 nurses. Data analysis using the Chai-Square test. The results of the study showed that there was a relationship between knowledge and nurses' preparedness in handling COVID-1 patients with a value of p=0.018, there was a relationship between education and nurses' preparedness in handling COVID-19 patients with a value of p=0.024, there was a relationship between age and nurses' preparedness in handling COVID-19 patients with a value of p=0.005, there was a relationship between length of work with nurses' preparedness in handling COVID-19 patients with a value of p=0.018. The majority of nurses' preparedness falls into the ready category with a frequency of 24 people (80.0%) while the category is not ready with a frequency of 6 people (20.0%).The conclusion in the study of factors related to nurse preparedness in handling COVID-19 patients in the Emergency Room is knowledge, education, age and length of work and nurse preparedness.